Self-templating synthesis of porous carbon with phytate salts for supercapacitor application. (January 2023) - Wang, Xin; Wang, Xinyi; Zhou, Xiaofeng; Yang, Xinping; Wu, Xiaozhong; Zhou, Pengfei; Zhou, Jin; Zhuo, Shuping
Abstract: Zinc phytate was synthesized as a self-sacrificing template to prepare porous carbon for supercapacitor with the starting materials of phytate acid and zinc acetate. The obtained carbon material possesses a hierarchically porous structure with pore size distributed at 1 and 10 nm, contributing to a specific surface area of 1125 m 2 g −1 according to the nitrogen sorption analysis. Moreover, the porous structure can be effectively adjusted by introducing KOH during the preparation procedure of phytate salt, resulting in a significant increase of micropore content. The absence of KOH signal in the X-ray diffraction pattern of carbon precursor and uniform K, Zn distribution in carbon precursor indicate the formation dual-metal phytates and contributing to the micropore for the prepared porous carbon by in-situ K activation instead of KOH activation. With developed microporosity, the specific capacitance can be promoted up to 294 from 195 F g −1 in KOH electrolyte and 247 from 187 F g −1 in H2 SO4 electrolyte. Our findings provide a guide to prepare porous carbon with tunable porosity through a facile self-templating method. Highlights: Phytate salt is synthesized and used as self-template to prepare porous carbon. The porosity is tuned by adding KOH during the preparation of phytate salts. The micropores are generated by in-situ K activation instead of KOH. The micropore surface area increases up to 936 from 307 m 2 g −1 . The specific capacitance reaches up to 294 from 195 F g −1 in KOH electrolyte.